2022
DOI: 10.1186/s41043-022-00325-7
|View full text |Cite
|
Sign up to set email alerts
|

Description of a telephone and Internet-based intervention to improve community responses to COVID-19 spread

Abstract: Background This paper describes the process and results of a health promotion intervention to engage lay communities using telephone and online communication, to improve their current responses to the spread of COVID-19. Methods An intervention was conducted from March to July 2020 in three districts of Sri Lanka. Seven ‘trigger’ stories were shared through telephone or online communication to stimulate brainstorming and to engage selected communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Many studies have shown that health education, psychological care, and humanistic care in the form of telephone communication and text messages after abortion can improve the physical and mental health of women after the intended abortion [ 12 15 ], and contraception provides a series of other potential benefits in addition to health, and some studies believe that it is necessary to promote various forms of health education models. Studies have indicated many benefits and possibilities of using mobile communication education methods for continuity services [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that health education, psychological care, and humanistic care in the form of telephone communication and text messages after abortion can improve the physical and mental health of women after the intended abortion [ 12 15 ], and contraception provides a series of other potential benefits in addition to health, and some studies believe that it is necessary to promote various forms of health education models. Studies have indicated many benefits and possibilities of using mobile communication education methods for continuity services [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%